Self medication among elderly poses challenges in urban settings - Hingorani, Sadhana K.; Desai, Anupama S.; Desai, Sakshi S.; Bansal, Raj Kumar; Agarwal, Shubham; Solanki, Naisargee; Desai, Ishaan (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Self-medication can be defined as obtaining and consuming one (or more) drug(s) without the advice of a physician. Using over the counter medicine is a common practice in developing countries including India. Studies have shown relatively high rates of self-medication among elderly and suggested awareness programmes among this group. Objectives of current study are to determine the prevalence of self-medication among geriatric population and to educate them about self-medication by an interactive session. Methods This was a cross sectional, questionnaire based study to evaluate the prevalence of self-medication in geriatric population in senior citizen club of Adajan and Ghoddod area of Surat city. Questionnaires were designed and modified from previous studies. Written informed consent was taken from those willing to participate in the study. After filling of pre-questionnaire, an interactive session was arranged and post-questionnaire were given to all participants. Data obtained were subjected to statistical analysis. Results: Number of participants in present study was 100. Self-medication was most common in age group of 65 to 75 years (48%) followed by less than 65 years (33%). 85% participants reported having taken non-prescription drugs. Drugs commonly used for self-medication were analgesics (85) and antacids (80). Side effects due to self-medication were reported by 22 participants. Main reasons for self-medication cited were to save expenses (65) and to save time (62). Post study awareness increased to 98%. Conclusions: Prevalence of self-medication is high in elderly. Interactive session can increase awareness regarding self-medication.